Orbital Fracture Repair - Grob, Seanna; Yonkers, Marc; Tao, Jeremiah (Seminars in Plastic Surgery, 2017)
Orbital fractures are very common after facial trauma. The assessment of a patient with a suspected orbital wall injury includes a detailed oculofacial examination as well as radiologic imaging. Surgical repair with or without an implant may be indicated for diplopia, enophthalmos, or both. Cicatricial eyelid malposition is an iatrogenic complication commonly due to poor orbitotomy technique. Optimal repair involves direct exposure of the perimeter of the fractures' site through surgical planes that minimally scar the eyelids. A wide variety of implant options exist; however, thin, pliable, nonadherent materials such as nylon foil may offer several advantages. The authors describe the evaluation and management of orbital wall fractures.
Keywords: orbit fracture; orbital floor; medial orbital wall; orbit implant; blow-out; enophthalmos; entrapment